Zakład Prawa Konkurencji i Regulacji Sektorowej - Szydło, Marek (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The Division of Competition Law and Sector-Specific Regulation, headed by Prof. Marek Szydło, is the youngest department within the Institute of Administrative Sciences. Its main fields of interest are: constitutional aspects of competition law and sector-specific regulation; various structural, procedural and substantive institutions of competition law and sector-specific regulation; electronic communications law; energy law; state aid law; public protection of consumers’ interests. Currently, the Division of Competition Law and Sector-Specific Regulation performs two scientific programs financed by the National Science Centre, entitled: “Judicial review of decisions made by national competition authorities and national regulatory authorities in light of EU law and national law”, and “The public supervision over the public procurement market”. The most valuable scientific achievements of the Division of Competition Law and Sector-Specific Regulation include the numerous scientific monographs of Prof. Szydło, as well as his scientific articles published in law journals indexed in prestigious Journal Citation Reports.
Keywords: Zakład Prawa Konkurencji i Regulacji Sektorowej; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia